Platform for High-Spin Molecules: A Verdazyl-Nitronyl Nitroxide Triradical with Quartet Ground State; Journal of the American Chemical Society (JACS); Vol. 143, iss. 21 - Tretjyakov E. V. Evgeny Viktorovich; Petunin P. V. Pavel Vasilievich; Zhivetjeva S. I. Svetlana Ivanovna; Gorbunov D. E. Dmitry Evgenjevich; Gritsan N. P. Nina Petrovna; Fedin M. V. Matvey Vladimirovich; Stas D. V. Dmitry Vladimirovich; Samoylova R. I. Rimma Ivanovna; Bagryanskaya I. Yu. Irina Yurjevna; Shundrina I. K. Inna Kazimirovna; Bogomyakov A. S. Artem Stepanovich; Kazantsev M. S. Maksim Sergeevich; et al. (2021, 2021)
Title screen